FROM â€œDEATHâ€ TO â€œLIFEâ€ â€“ ×Ö¼Ö¸ ×“ IN THE PSALMS: A LEXICAL-SEMANTIC-CULTURAL SURVEY, WITH SPECIAL REFERENCE TO THE TRANSLATION OF â€œBLOODâ€ IN A WESTERN AND AN AFRICAN SETTING - Wendland, Ernst (Journal for Semitics, 2017)
After a brief lexical-semantic summary of the principal senses of ×Ö¼Ö¸ ×“ in the Hebrew Bible (HB), our focus shifts to this wordâ€™s 21 occurrences in the Psalms. How widely and diversely was the notion of â€œbloodâ€ employed in the psalmistsâ€™ manifold prayers to the Lord? We then consider the practice of translation in two greatly contrasting sociocultural settings â€“ Western versus African. What are some of the main challenges that translators confront when they attempt to convey the distinct â€œmeaningsâ€ of ×Ö¼Ö¸ ×“ meaningfully â€“ with functionally equivalent content, intent, impact and appeal â€“ in these two disparate contexts? In a Western setting, as expressed in English, the biblical, symbolically sacred understanding of â€œbloodâ€ is virtually non-existent, thus necessitating significant paratextual supplementation, whereas in an African linguistic environment, Chichewa for example, the ancient symbolical sense of â€œbloodâ€ and its contemporary connotations remain so powerful that it requires great care in translation in order to avoid possible misunderstanding or offense in the vernacular text. In the latter case and in certain Psalmic passages, it turns out that instead of some expression relating to â€œdeathâ€, one that rather conveys the notion of â€œlifeâ€ may well be more accurate and acceptable, especially when uttered in prayer or praise to the Lord.